Legal Certainty of Execution of Pledged Objects Against Marital Assets as Collateral for Debt Without Spouse's Consent - Salam, Ruby (Jurnal Konstatering, 2026)
Marriage creates legal relationships, one of which concerns joint property. Article 36 Paragraph 1 of Law Number 16 of 2019 concerning Marriage mandates that husband and wife have equal rights regarding joint property. Furthermore, any legal action related to joint property must be based on the agreement of both parties. In this regard, pawnshops are one of the non-bank financial institutions that provide a quick solution for the community to meet immediate funding needs, with gold jewelry as collateral. This study aims to find out: How is the execution of pawned objects in the form of gold jewelry which is joint property from a marriage bond that is used as collateral for debt without the consent of the case study partner at PT. Pengadaian Cabang Teluk Betung?, and How is the legal certainty of the execution of the pawned object against marital assets in the form of gold jewelry that is used as collateral for debt without the consent of the spouse (Study at PT. Pegadaian Teluk Betung Branch)? This research uses an empirical approach, using secondary and primary data, obtained from literature studies and field studies by means of interviews. Based on the research, it is concluded: the legal certainty of the regulation of pawned objects whose goods are joint assets in marriage which are used as collateral for debt without the consent of the husband or wife is contained in Article 36 paragraph (1) of Law No. 16 of 2019 concerning Marriage which has provided a legal corridor, that the action to pawn joint assets must be based on the agreement of both parties between husband and wife. As with Gustav Radbruch's theory of legal certainty that legal certainty is one of the objectives of the law itself, the process of executing pawned objects in the form of marital assets which are used as collateral for debt without the consent of the spouse at the Pawnshop is null and void. Suggestion: There needs to be strict regulation from the institutional structure that oversees financial institutions and financial services in Indonesia, such as Bank Indonesia and the Financial Services Authority of the Republic of Indonesia, because there is already a legal umbrella based on Article 36 paragraph (1) of Law No. 16 of 2019 concerning Marriage and the Need to provide strong legal protection to both husband and wife, it is best to make a prenuptial agreement regarding the property they own.